Pictorial Atlas of Fossil and Extant Horseshoe Crabs, With Focus on Xiphosurida - Bicknell, Russell D. C.; Pates, Stephen (Frontiers in Earth Science, 2020)
Horseshoe crabs (Xiphosura sensu lata) are one of the most iconic groups of extant chelicerates, with a stunning fossil record reaching back to at least the Lower Ordovician (~480 million years ago). As such, the group has maintained a significant biological and palaeontological interest. Due to the sporadic nature of descriptive and systematic work on fossil horseshoe crabs over the last century information on this group is spread over tens of publications spanning over 100 years. To rectify this, we present the most comprehensive pictorial atlas of the taxa to date. This review highlights taxa that have not been examined for decades, including ‘Bellinurus’ carterae, Bellinurus lacoei, Kiaeria limuloides, Limulus priscus and Prolimulus woodwardi that have never been documented with photography. Furthermore, key morphological features of the true horseshoe crab (Xiphosurida) families: Austrolimulidae, Belinuridae, Limulidae, Paleolimulidae, and Rolfeiidae are described. The evolutionary history of the group is reviewed and the current issues facing any possible biogeographic work are presented. Five major future directions that can be explored for horseshoe crab researchers are outlined and it is highlighted that this review provides the basis for complete phylogenetic, geographic, and morphometric studies.